2021
DOI: 10.3390/genes12091364
|View full text |Cite
|
Sign up to set email alerts
|

The Multiple Facets of Iron Recycling

Abstract: The production of around 2.5 million red blood cells (RBCs) per second in erythropoiesis is one of the most intense activities in the body. It continuously consumes large amounts of iron, approximately 80% of which is recycled from aged erythrocytes. Therefore, similar to the “making”, the “breaking” of red blood cells is also very rapid and represents one of the key processes in mammalian physiology. Under steady-state conditions, this important task is accomplished by specialized macrophages, mostly liver Ku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 166 publications
0
29
0
1
Order By: Relevance
“…Since the unique architecture of the spleen confers a filter for verifying the biomechanical integrity of RBCs (Mebius and Kraal, 2005; Slusarczyk and Mleczko-Sanecka, 2021), we observed only local but not systemic dyshomeostasis of RBCs during aging. Most importantly, we found that splenic RBCs of aged mice show ROS accumulation, a characteristic feature of senescent RBCs, and a risk factor for enhanced hemolysis (Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Since the unique architecture of the spleen confers a filter for verifying the biomechanical integrity of RBCs (Mebius and Kraal, 2005; Slusarczyk and Mleczko-Sanecka, 2021), we observed only local but not systemic dyshomeostasis of RBCs during aging. Most importantly, we found that splenic RBCs of aged mice show ROS accumulation, a characteristic feature of senescent RBCs, and a risk factor for enhanced hemolysis (Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 88%
“…2A). However, defective RBCs are first filtered in the spleen due to the loss of their elasticity, and this step is a prerequisite for their removal via EP (Slusarczyk and Mleczko-Sanecka, 2021). In agreement with this model, RBCs that are retained in the spleen of young mice show ROS build-up, a marker of their senescence (Bratosin et al, 1998), compared to the circulating RBCs (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations